C–H Trifluoromethylthiolation of aldehyde hydrazones - Levet, Victor; Ramesh, Balu; Wang, Congyang; Besset, Tatiana (Beilstein Journal of Organic Chemistry, 2024)
The selective C–H trifluoromethylthiolation of aldehyde hydrazones afforded interesting fluorinated building blocks, which could be used as a synthetic platform. Starting from readily available (hetero)aromatic and aliphatic hydrazones, the formation of a C–SCF3 bond was achieved under oxidative and mild reaction conditions in the presence of the readily available AgSCF3 salt via a one-pot sequential process (28 examples, up to 91% yield). Mechanistic investigations revealed that AgSCF3 was the active species in the transformation.
Keywords: C–H bond functionalization; C–S bond formation; hydrazones; synthetic method; trifluoromethylthiolation